Perkembangan Geologi pada Kuarter Awal sampai Masa Sejarah di Dataran Yogyakarta - Sri Mulyaningsih; Sampurno Sampurno; Yahdi Zaim; Deny Juanda Puradimaja; Sutikno Bronto; Darwin Alijasa Siregar (Geological Agency, 2006)
http://dx.doi.org/10.17014/ijog.vol1no2.20065The uplift of Southern Mountains in Early Pleistocene has formed the Yogyakarta Basin. In this basin, the Merapi volcanic activity has been developing. Based on 14C dating in cinder deposits exposed at Cepogo, the volcanic activity took place since ±42 ka. While on the basis of K/Ar dating in andesitic lava at Bibi Volcano, the activity took place since 0.67 ma. The high in the south and the appearance of Merapi volcanic dome in the north had caused a fl at valley. The southern part of the valley is bounded by the Southern Mountains and the western part is bounded by the West Progo Mountains. In the present time, the lithology of the areas which are interpreted as a palaeo-valley is composed of black clay deposits. This black clay is a contact between the basement rocks and Merapi volcanic deposits. The black clay deposits exposed in the Progo River (Kasihan) has been developed since ±16.59 to 0.47 ka, while in the Opak River (Watuadeg) 6210 y BP. Younger black clay deposits intersecting with lahars are also exposed at the Winongo River and have an age of 310 y BP. The age data of volcanic stratigraphy shows that Merapi activities had taken place since ±6210 up to ±310 years ago.